Competitiveness of Malaysian Exports - Tham Siew-Yean (Kajian Malaysia, 2001)
Given the importance of Malaysian manufacturing exports before and after the economic crisis in 1997, the paper seeks to assess the ability of Malaysian manufacturing exports to compete as well the sources of competitiveness. It was found that Malaysian export of high technology products has grown tremendously between 1989-98. However these exports are concentrated in only 2 product groups. The main competitors from within ASEAN countries are Singapore, Philippines and Thailand while outside ASEAN, China is also rapidly catching up in high technology exports. Foreign direct investment was found to be a relatively important source of competitiveness as compared to the exchange rate. Thus, key domestic issues thaL, can affect the future competitiveness of Malaysian exports are the exchange rate policy, FDI policy, export diversification as well as human capital development. On the external front, competitive pressures from China, the future of the Japanese economy as well as the progress of global liberalization will also have important bearings on the ability of Malaysian exports to compete in the future. Memandangkan pentingnya eksport perkilangan Malaysia sebelum dan selepas kegawatan ekonomi dalam tahun 1997, kajian ini cuba meneliti keupayaan eksport perkilangan negara untuk bersaing dan seterusnya sumber daya saingan eksport tersebut. Hasil kajian ini menunjukkan pertumbuhan eksport barang berteknologi tinggi telah bertambah pesat an tara 1989-98. Bagaimanpun, eksport tersebut hanya bertumpu kepada 2 kategori produk. Pesaing dalam ASEAN yang dihadapi oleh eksport Malaysia ialah Singapura, Filipin dan negara Thai manakala dari luar ASEAN ialah negara Cina yang juga mengalami pertumbuhan pesat dalam eksport barang berteknologi tinggi. Pelaburan langsung asing merupakan satu sumber daya saing yang relatif penting berbanding dengan kadar pertukaran asing. Justeru itu, isu domestik yang boleh mempengaruhi daya saing barang perkilangan pada masa depan ialah dasar kadar pertukaran, dasar pelaburan langsung asing, pelbagaian eksport, dan pembangunan modal manusia. Di peringkat luar negara, daya saing dari negara Cina, masa depan ekonomi negara Jepun dan juga perkembangan liberalisasi secara global juga akan menentukan keupayaan eksport Malaysia untuk bersaing pada masa depan.